Analysis Of Employee Work Discipline At PT. Bussan Auto Finance (BAF) Sumedang Branch - Aulia Akbar; Ryan Feryana Kurniawan; Solihin Royani (SINTESA, 2022)
The focus of this research is to analyze how the implementation of Employee Work Discipline at PT. Bussan Auto Finance (BAF) Sumedang Branch. This study aims to determine Work Discipline and what efforts are made to improve Work Discipline at PT. Bussan Auto Finance (BAF) Sumedang Branch. The method used in this study is a qualitative research method. According to Steven Dukeshire & Jennifer Thurlow (Sugiyono, 2020: 3) stated that qualitative research is concerned with data that is not numbers, collecting and analyzing narrative data. Meanwhile, in analyzing the data, the researcher uses the data analysis method of the Miles and Huberman model, the activities in the data analysis which include data collection, data reduction, data presentation, and drawing conclusions. The theory of this research and the dimensions used from the theory according to Bejo Siswanto (Sinambela, 2019:356) are indicators that affect work discipline including frequency of attendance, level of alertness, obedience to work standards, obedience to work regulations, and work ethics. Based on the results of interviews, observations and data analysis, it was concluded that Work Discipline at PT. Bussan Auto Finance (BAF) Sumedang Branch as a whole has been running quite well in accordance with the SOP (Standard Operating Procedure) and company regulations. While suggestions that can be used as material for further consideration is that in the application of employee work discipline, participation between superiors and employees is needed in enforcing discipline. PT. Bussan Auto Finance (BAF) Sumedang Branch should further emphasize the sanctions given to employees who commit violations, in order to provide a deterrent effect and so that employees do not repeat the same mistakes